(untitled) (Revista de Ciências Agroveterinárias, 2018)
This study determined the occurrence of parvovirus and distemper in dogs treated at the Veterinary Clinics Hospital (HCV) of Universidade Estadual de Santa Catarina (UDESC). For such, 3198 medical records filed in the HCV, from February 2013 to July 2015, were reviewed. From the records, 145 (4.53%) dogs were diagnosed with parvovirus (76 [2.38%]) or distemper (69 [2.15%]). The most common clinical signs of parvovirus were gastrointestinal signs (76 [100%]), having hematochezia as the most commonly observed (74 [97.37%]); for distemper, neurological signs (48 [69.56%]) were most frequently described and myoclonus had the highest occurrence (31 [64.58%]). Regarding complete blood count, the most observed variation in parvovirus was leukopenia by neutropenia and lymphopenia (20 [71.43%]). Distemper showed lymphopenia (28 [59.57%]). It was also observed that the occurrence of distemper and parvovirus were higher according to some selection criteria: breed, age, outdoor access, having contact with other animals and vaccination status. Young non-vaccinated dogs with outdoor access had the highest occurrence ratio. This study showed that viral infectious diseases presented low occurrence, and parvovirus was the most reported agent.